A Hybrid Nanofiber/Paper Cell Culture Platform for Building a 3D Blood–Brain Barrier Model. Issue 9 (16th August 2021) - Huang, Kaixiang; Castiaux, Andre D.; Podicheti, Ram; Rusch, Douglas B.; Martin, R. Scott; Baker, Lane A.
Abstract: The blood–brain barrier (BBB) protects the central nervous system from toxins and pathogens in the blood by regulating permeation of molecules through the barrier interface. In vitro BBB models described to date reproduce some aspects of BBB functionality, but also suffer from incomplete phenotypic expression of brain endothelial traits, difficulty in reproducibility and fabrication, or overall cost. To address these limitations, a 3D BBB model based on a hybrid paper/nanofiber scaffold is described. The cell culture platform utilizes lens paper as a framework to accommodate 3D culture of astrocytes. An electrospun nanofiber layer is coated onto one face of the paper to mimic the basement membrane and support growth of an organized 2D layer of endothelial cells (ECs). Human induced pluripotent stem cell‐derived ECs and astrocytes are co‐cultured to develop a human BBB model. Morphological and spatial organization of model are validated with confocal microscopy. Measurements of transendothelial resistance and permeability demonstrate the BBB model develops a high‐quality barrier and responds to hyperosmolar treatments. RNA‐sequencing shows introduction of astrocytes both regulates EC tight junction proteins and improves endothelial phenotypes related to vasculogenesis. This model shows promise as a model platform for future in vitro studies of the BBB. Abstract : The authors describe a cell culture platform comprised of paper coated with electrospun nanofibers. Culture of a 2D endothelial cell layer atop a nanofiber layer and 3D astrocytes within the paper fibers creates a unique blood–brain barrier model. Characterization via microscopy, resistance and permeability measurements, and differential gene expression underscore the promise of this model for blood–brain interface studies.